2014
DOI: 10.1063/1.4873140
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing temperature on the contact properties of Ni/V/4H-SiC structure

Abstract: A sandwich structure of Ni/V/4H-SiC was prepared and annealed at different temperatures from 650 °C to 1050 °C. The electrical properties and microstructures were characterized by transmission line method, X-ray diffraction, Raman spectroscopy and transmission electron microscopy. A low specific contact resistance of 3.3 × 10-5 Ω·cm2 was obtained when the Ni/V contact was annealed at 1050 °C for 2 min. It was found that the silicide changed from Ni3Si to Ni2Si with increasing annealing temperature, while the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Many researchers have indicated that the operation lifetime of the SiC devices is strongly affected by the stability of the metal/SiC contact when operating in high temperature environment. 28,29) In general, Ni is known as a good candidate to form ohmic contact to n-type 4H-SiC because of low specific contact resistance. However, it has been reported that, during the annealing process at high temperature, Ni reacts with Si in the SiC substrate and forms Ni x Si y compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have indicated that the operation lifetime of the SiC devices is strongly affected by the stability of the metal/SiC contact when operating in high temperature environment. 28,29) In general, Ni is known as a good candidate to form ohmic contact to n-type 4H-SiC because of low specific contact resistance. However, it has been reported that, during the annealing process at high temperature, Ni reacts with Si in the SiC substrate and forms Ni x Si y compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[8][9][10][11] It has been reported that the operation lifetime of the SiC-based devices is not limited by the semiconductor properties itself, however, it is strongly governed by the reliability of the metal/SiC contacts. [12][13][14][15][16] A. V. Kuchuk et al reported that the Au/Ni 2 Si/n-SiC contact completely failed after 150 h of aging at 400 °C because of the interdiffusion/ reaction processes in the contact. 17) Therefore, fabrication ohmic contact with low specific contact resistivity and high temperature reliability is a critical issue that needs to be overcome to introduce SiC devices into reality.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] However, much of the literature has indicated that reliable operation of SiC-based electronic devices is not limited by the electronic properties of the semiconductor itself but is strongly affected by the reliability and stability of the metal/SiC contacts. [11][12][13][14][15] For these reasons, fabrication of ohmic contacts to SiC with low specific contact resistivity and high-temperature stability is critical for applications in harsh environments.…”
Section: Introductionmentioning
confidence: 99%
“…This carbon agglomeration was reported to cause a higher surface roughness, increasing the contact resistance and the degradation of the devices when operating in a high-temperature environment. 13,[29][30][31][32] To solve this problem, a Ni-based multilayer with other metallic elements has been investigated. The added metal should have ability to react with the carbon and form a stable metal carbide.…”
Section: Introductionmentioning
confidence: 99%